Rola kontekstu społecznego oraz czynników indywidualnych w rozwijaniu kompetencji różnojęzycznej polskich gimnazjalistów - Kucharczyk, Radosław (Neofilolog, 2017)
The aim of this article is to reflect on the role of social context and individual factors that influence the development of multilingual competence. The first part of the article deals with the analysis of the definition of the multi-lingual competence and its role in language teaching. The next part is the presentation of the relation between the social and educational context, taking into consideration students’ individual features and multilingual competence. The last part of the article consists of the analysis of the results of the research study conducted among Polish Junior High School students. The aim of the study was to establish the impact of different factors influencing learning French as the second language.